Understanding Paintings: The Icon as a Paradigm - Rudd, Anthony (Religion and the arts, 2018)
AbstractHans-Georg Gadamer has claimed, first, that in religious painting the image does not merely copy its prototype but is in "ontological communion" with it; and second, that in this respect the religious painting is exemplary for painting in general. I examine these claims with specific reference to Eastern Orthodox icons, drawing on both classical and modern Orthodox theological accounts of the icon to support and amplify Gadamer's claim about "ontological communion." I then consider accounts by Jean-Luc Marion and by the theologian Paul Evdokimov of how the icon can be exemplary for painting in general. I argue that Marion's discussion leads to some unacceptable conclusions, and that Evdokimov provides a more convincing account. This commits him to a strong and controversial thesis that all art (consciously or otherwise, and whatever its explicit subject-matter) is in a sense religious.